2018
DOI: 10.1021/acsaem.8b00957
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Coordination Sphere Geometry of Copper Redox Mediators on Regeneration and Recombination Behavior in Dye-Sensitized Solar Cell Applications

Abstract: The recombination of injected electrons with oxidized redox species and regeneration behavior of copper redox mediators are investigated for four copper complexes, [Cu(dmby) 2 ] 2+/1+ (dmby = 6,6′-dimethyl-2,2′bipyridine), [Cu(tmby) 2 ] 2+/1+ (tmby = 4,4′,6,6′-tetramethyl-2,2′-bipyridine), [Cu(eto) 2 ] 2+/1+ (eto = 4-ethoxy-6,6′-dimethyl-2,2′-bipyridine), and [Cu-(dmp) 2 ] 2+/1+ (dmp = bis(2,9-dimethyl-1,10-phenantroline). These complexes were examined in conjunction with the D5, D35, and D45 sensitizers, havi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
81
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 54 publications
(87 citation statements)
references
References 57 publications
(125 reference statements)
5
81
1
Order By: Relevance
“…Perhaps most strikingly, the increase in V OC from C 3 to C 3 –CDCA was measured at 60 mV. In other studies, the use of longer alkoxy chains has produced the same V OC ‐enhancing behavior, and thus we conclude that the CDCA substituent blocks electron recombination from TiO 2 to the electrolyte and thereby improves the photovoltage. This is supported by a slight improvement in electron lifetimes (see Figure c).…”
Section: Resultssupporting
confidence: 64%
“…Perhaps most strikingly, the increase in V OC from C 3 to C 3 –CDCA was measured at 60 mV. In other studies, the use of longer alkoxy chains has produced the same V OC ‐enhancing behavior, and thus we conclude that the CDCA substituent blocks electron recombination from TiO 2 to the electrolyte and thereby improves the photovoltage. This is supported by a slight improvement in electron lifetimes (see Figure c).…”
Section: Resultssupporting
confidence: 64%
“…Our data experimentally confirms the theoretical prediction of a pentacoordinated complex by Saygili et al based on DFT calculations. [ 62 ] This coordination has major implications for the redox chemistry and hence the performance of [Cu(dmp) 2 ] +/2+ as a redox couple in DSCs which will be discussed in further detail later.…”
Section: Resultsmentioning
confidence: 99%
“…Using density functional theory (DFT) calculations, Saygili et al predicted a coordination of tBP to the [Cu(dmp) 2 ] 2+ complex and have suggested that this coordination induces the shift in rest potential with respect to the tBP‐free solution. [ 62 ] The induced shift in redox potential caused by coordination with electrolyte additives has been speculated to be a crucial factor for the success of these redox mediators, by significantly reducing the driving force for recombination and therefore allowing for the high open‐circuit voltage ( V OC ) values reported. Very recently, Kannankutty et al studied the coordination of tBP to [Cu(dmp) 2 ] 2+ using absorption and 1 H‐NMR spectroscopy and concluded that [Cu(dmp) 2 (TBP)(MeCN) x ] 2+ (with x = 0, 1) is the most likely species in the electrolyte mixture.…”
Section: Introductionmentioning
confidence: 99%
“…The electrochemical properties of copper complexes strongly rely on the chelating ligands, since the coordination sphere impacts the redox potentials and the reorganisation between Cu(I) and Cu(II) ions [28]. For example, incorporation of bulky groups into neighboring sites of the chelating atoms exerts a remarkable steric hindrance effect to the Cu(I)/Cu(II) redox shuttle for Cu(I) complexes [11,29], which lowers the reorganisation energies and therefore the structural changes between copper I and II, which subsequently leads to more efficient charge transfer between the sensitizer and the redox species [30].…”
Section: Fundamental Aspects Of Copper Coordination Complexesmentioning
confidence: 99%